Role of methotrexate chronotherapy in collagen-induced rheumatoid arthritis in rats - Wang, X. (Z Rheumatol, 2016)
AIM: To explore the circadian rhythm of serum interleukin (IL)-6 in collagen-induced arthritis (CIA) rats and compare the safety and effectiveness of methotrexate (MTX) administered traditionally and via chronotherapy. METHODS: CIA rat models were immunized with bovine type II collagen. Serum IL-6 levels in normal and CIA rats were measured at 2, 6, 10, 14, 18, or 22 h after the light was turned on (HALO). MTX was administered to 6 HALO/18 HALO experimental groups of Wistar rats once daily according to the IL-6 rhythm. The control groups (positive, negative, and normal) were given MTX or an equal volume of phosphate buffered saline (PBS) once a week simultaneously. Arthritis score, tumor necrosis factor (TNF)-α, interleukin (IL)-6, and C reactive protein (CRP) levels in the serum were measured by enzyme-linked immunosorbent assay (ELISA). Histological changes in the ankle joint were analyzed. RESULTS: After 6 weeks of treatment, arthritis scores in the experimental group were lower than in the control group. The expression of TNF-α, IL-6, and CRP was lower in the 18 HALO group than in the control or 6 HALO groups. Histopathology scores in the experimental groups were lower than in the control group (p < 0.05). CONCLUSION: The plasma IL-6 levels in CIA rats were higher than in normal rats and showed significant circadian rhythm. Daily administration of MTX is more potent than weekly administration. The therapeutic index of rheumatoid arthritis (RA) may be improved with MTX therapy based on the IL-6 circadian rhythm.